POTENCY OF GEL SODIUM SILICATE/UREA FOR WATER SHUT-OFF TREATMENT IN ENHANCED OIL RECOVERY (EOR) - Fakhri, Afiq
The need for fuel oil increases, while the amount of oil reserves in Indonesia decreases. Exploration of new oil wells is very expensive, therefore efforts of increasing the oil production in old wells through EOR ( Enhanced Oil Recovery) are still developed. One way to increase the oil recovery is known as water shut-off where chemicals are injected in old wells to avoid the excess water production (water conning). The purpose of this research is to prepare a gel of sodium silicate/urea used as a blocking agent in the water shut-off technique and to study the effects of their concentration and temperature on the gelation time. The range of the sodium silicate concentration studied in this research was between 3.99 to 21.44% w/w, the urea concentration between 5 to 20% w/w, the concentration of salt between 0.5 to 3% w/w, whereas temperature was varied between 65 to 120 °C. It was found that higher concentration of urea and sodium silicate resulted in faster gelation time. At the concentration of sodium silicate between 3.99-10.72% w/w a gel was formed, but at higher concentration a white suspension. The optimum concentration of urea was obtained at 5% w/w and the maximum salinity tolerance was 2% w/w. At the salinity > 2% w/w and sodium silicate > 6.7% w/w, a suspension was also formed. The higher the temperature, the faster the gelation time. The optimum temperature was achieved at ? 95 °C. It can be concluded that the concentration of chemicals and temperature affected the gelation time and the sodium silicate/urea gel reduced the permeability and porosity of the core drastically.